THE POSITION FILLING OF PRATAMA HIGH LEADERSHIP IN CIANJUR REGENCY UNDER GOOD GOVERNANCE CONCEPT - Tanti Kirana Utami (Faculty of Law, Universitas Jenderal Soedirman, 2017)
A fundamental change in terms of structuring government apparatus particularly position filling of pratama high leadership in local agencies openly aimed to realize good governance. This paper examines the application of open systems in position filling of pratama high leadership of regional secretary in Cianjur and the government's readiness of Cianjur regency in the implementation of position filling of pratama high leadership (regional secretary). This research applied normative juridical approach by descriptive analysis while the analysis of data used triangulation method. The results of this study are the position filling of pratama high leadership (regional secretary) in Cianjur already introduced an open and competitive system by forming a selection committee to establish and coordinate with the State Civil Administrative Commission in the implementation of the administration and the competence of official candidates. In filling the position of high leadership, a regulation of sanctions and rewards for position of pratama high leadership related to the performance is required.Keywords: position of Pratama high leadership, open system, good governance